Pembinaan Remaja Putus Sekolah Untuk Meningkatkan Motivasi Sekolah Di Desa Teloke Tengah Kecamatan Batulayar - Ni Made Sulastri; Dewi Rayani; Herman Syah (Jurnal Pengabdian kepada Masyarakat Cahaya Mandalika (Abdimandalika), 2024)
Education has a strategic role in preparing a quality generation for the benefit of the future. The importance of educational awareness determines the quality of future physical and spiritual social welfare. Education has a strategic role in preparing a quality generation for the benefit of the future. Considering the importance of knowledge and the limitations of families in providing knowledge, parents are reluctant to continue their education to their children, thereby increasing the school dropout rate. The ever-increasing school dropout rate results in various criminal acts such as theft, robbery, murder and others which disturb the community and the peace that has existed in society will be lost. So it is necessary to provide guidance for unemployed teenagers to increase school motivation in Toleke Tengah village, Batulayar sub-district. The method used in this community service activity is in the form of coaching, this community service activity includes coaching from an academic, psychological and religious, social and community perspective. The results of implementing this activity are an understanding of the delivery of the material and an increase in teenagers' desires. drop out of school to continue their education which has been postponed.